Museum and Archive on the Move: Changing Cultural Institutions in the Digital Era - Grau, Oliver; Coones, Wendy; Rühse, Viola (De Gruyter, 2017)
The digital revolution fundamentally changed how cultural heritage is created, documented, analyzed, and preserved.The book focuses on this transformation's impact.How must museums and archives meet the challenges of digitally generated cultures and how does the digital revolution influence traditional object collection, research, and education?.